An Analysis of Feminism Idea that represented by Queen Elizabeth I in the Shekhar Kapur's Film Entitled 'Elizabeth: The Golden Age' - Handika, Manda; Hartiningsih, Sri (University of Muhammadiyah Malang, 2014)
An Analysis of Feminism Idea that represented by Queen Elizabeth I in the Shekhar Kapur's Film Entitled 'Elizabeth: The Golden Age'